Optimal Portfolio Strategy of Mutual Funds from Schroders Investment Indonesia for the Period of 2013-2015 - Kusumawardani, Andika Setya; Murtaqi, Isrochmani (Journal of Business and Management, 2017)
Abstract. This thesis aims to generate the strategy to achieve the optimum portfolio of mutual funds from Schroders Investment Indonesia for the period of 2013-2015 refers to Markowitz’s portfolio theory. As the data,   author uses 5 mutual funds from Schroders Investment Indonesia, Jakarta Composite Index from 2013-2015, and also Bank Indonesia rate from 2013-2015. The author will construct 3 portfolio strategies; there are Maximum Return Portfolio, Minimum Standard Deviation Portfolio, and Maximum Sharpe Ratio Portfolio. The author uses Microsoft Excel Solver add-ins in creating the portfolio and weight of each mutual fund in the portfolio. The portfolio’s performance is analyzed compare to the market using Sharpe ratio. Based on the calculation among 3 portfolios, the portfolio that gives the best performance is Maximum Sharpe Ratio Portfolio which achieves highest Sharpe Ratio that fulfills the Markowitz’s optimum portfolio theory. The portfolio generates 0.029% of average daily return and 0.447% of average daily standard deviation. This research generates the strategy of optimum portfolio mutual funds from Schroders Investment Indonesia based on Markowitz’s portfolio theory. Keywords: Markowitz Portfolio Theory, Mutual Fund, Optimum Portfolio, Schroders Investment Indonesia, Sharpe Ratio